Rethinking Brand Identity to Become an Iconic Brand - A Study on Pepsi - Hafiz, Reaz (Asian Business Review, 2015)
One of the leading brands, Pepsi has battled time to time for getting success in the Cola industry by developing different slogans, ideas, celebrity endorsement, campaigns and other marketing efforts. These never ending quests for growth and market share are not always ended with positive notes because of miss fire of strategies. The focus of the paper is to identify current position and rebranding issues regarding Pepsi along with the ways to make it an iconic brand. In the first part of this paper, Holt’s concept has been used to analyze Pepsi Cola’s history and current position to establish whether and if yes to which extent this brand has managed to become iconic. The second part is dedicated towards developing and suggesting a future course of action for the company that would enable it once again becoming an iconic brand. JEL Classification Code:  M31
Keywords: Pepsi; Brand Identity; Rebranding; Myth